Evolution of learning models and spaces in the history of islamic education: from the Prophetic Era to the Sultanate period in Nusantara - Firmansyah Rangga; Nangkula Utaberta; Sumarni Ismail; Nayeem Asif (Journal of Islamic, Social, Economics and Development, 2025)
This study explores the historical evolution of learning models and spaces in Islamic education, from the Prophetic era to the Indonesian Sultanate period. Employing a qualitative methodology grounded in a comprehensive review of historical documents and relevant literature, the research analyzes the transformation of pedagogical practices and learning environments.The findings reveal a diverse array of learning models, commencing with the halaqah gatherings prevalent during the Prophetic era, typically centered in mosques, and culminating in the bandongan and sorogan systems characteristic of pesantren (Islamic boarding schools) during the sultanate period. The study further elucidates the development of learning spaces, from the initial reliance on mosques and scholars' residences to the emergence of formal institutions such as madrasahs (Islamic schools) and pesantren. Moreover, the research identifies key social, political, economic, and religious factors that influenced these evolutionary shifts. This study contributes to a deeper understanding of the historical tapestry of Islamic education and offers insights for the development of pedagogically relevant learning models in contemporary contexts.